2020
DOI: 10.18502/ijm.v12i2.2617
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the antimicrobial properties of nanoclay and chitosan based nanocomposite on the microbial characteristics of Gouda cheese

Abstract: Background and Objectives: In recent years, active packaging has been introduced as a new method to better preserve food. Chitosan and nanoclay have been used for preparation of an active nanocomposite with respect to their antimicrobial properties to investigate its effects on the microbial limitation in Gouda cheese. Materials and Methods: Nanoclay film, chitosan film, chitosan-based nanocomposites and nanoclay-based nanocompos- ites were prepared and their antimicrobial properties were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…They have reported that the water vapor permeability and oxygen permeability of PEnanocomposite films were 6.24 g/m 2 /24 h and 3017.5 cm 3 / (m 2 /24 h/0.1 MPa), respectively. According to Mohammadzadeh-Vazifeh et al (2020), incorporation of 1% nanoclay in the composite films has shown more antimicrobial activity (i.e. effective against gram-negative bacteria, yeast and mold) during storage of Gouda cheese.…”
Section: Total Plate Countmentioning
confidence: 99%
“…They have reported that the water vapor permeability and oxygen permeability of PEnanocomposite films were 6.24 g/m 2 /24 h and 3017.5 cm 3 / (m 2 /24 h/0.1 MPa), respectively. According to Mohammadzadeh-Vazifeh et al (2020), incorporation of 1% nanoclay in the composite films has shown more antimicrobial activity (i.e. effective against gram-negative bacteria, yeast and mold) during storage of Gouda cheese.…”
Section: Total Plate Countmentioning
confidence: 99%
“…The smell of an acid-curd cheese-like quark usually becomes more intense during storage [ 22 ] as does the flavor of gouda [ 17 ]. Therefore, the smell of both cheese varieties wrapped in the active film was less appreciated by panelists than that of control.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast and molds are typical microorganisms that cause spoilage of gouda and quark [17,43]. The use of the FUR + AgNPs film significantly influenced the number of yeast during cheese storage.…”
Section: Microbiological Quality Of Cheesementioning
confidence: 99%
See 2 more Smart Citations